ORGANOGENESIS TANAMAN ANGGUR HIJAU (VITIS VINIFERA L.) PADA MEDIUM MSDENGAN PENAMBAHAN IAA (INDOLE ACETID ACID) DANBERBAGAI KONSENTRASI BAP (BENZIL AMINO PURIN) - Tajuddin, Riska; Suwastika, I Nengah; Muslimin, muslimin (Natural Science: Journal of Science and Technology, 2012)
Research onorganogenesisof Grape (Vitis viniferaL.) on MS medium supplemented with IAA and various sconcentrations of BAP, was conducted at the Tissue Culture Laboratory, Faculty of Forestry Untad Palu, during periode of Januari and April 2012.This research was aimed to obtain the best combination ofIAA and BA Pin MS medium that stimulate organogenesis of Grape. This experiment was arranged in completely randomized design with 4 treatments and 3 replications.The treatmentswere: MS medium+ 0.1ppm IAA+ 0.1 ppm BAP(B1), MS medium+ 0.1 ppm IAA +0.3 ppm BAP (B2), MS medium + 0.1ppm IAA + 0.5ppm BAP(B3) and MS medium+ 0.1 ppm IAA+0.7BAP(B4). Parameters observed in this study were the days appear of shoots, the days appear of leaves, percentage of explant producing shoots (%), and the presence or absence of roots. The results showedthat MS medium+ 0.1 ppm IAA+0.7ppm BAP(B4) gived the best results in speedupof shootsandleaves,in 7 days after induction.